2014
DOI: 10.3389/fimmu.2014.00581
|View full text |Cite
|
Sign up to set email alerts
|

The Subtleties and Contrasts of the LeuO Regulator in Salmonella Typhi: Implications in the Immune Response

Abstract: Salmonella are facultative intracellular pathogens. Salmonella infection occurs mainly by expression of two Salmonella pathogenicity Islands (SPI-1 and SPI-2). SPI-1 encodes transcriptional factors that participate in the expression of virulence factors encoded in the island. However, there are transcriptional factors encoded outside the island that also participate in the expression of SPI-1-encoded genes. Upon infection, bacteria are capable of avoiding the host immune response with several strategies that i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 117 publications
0
8
0
Order By: Relevance
“…Additionally, studies found that cse1 from this bacterium was expressed in specific growth condition (N-minimal medium) [27], which promoted the expression of the Salmonella pathogenicity island 2 genes [28]. Furthermore, the S. Typhi CRISPR-Cas locus is regulated by LeuO (LysR-type regulator), H-NS (heat-stable nucleoid-structuring protein), and LRP (leucine-responsive regulatory protein) [27,29], which are involved in pathogenesis [30][31][32][33][34][35]. The cas genes of the type I-C CRISPR-Cas system in Myxococcus xanthus seem to be strongly embedded within the regulatory circuits that control the fruiting-body formation process and are tightly regulated by various intercellular quorum-sensing (QS) signals and intracellular signaling cascades [36,37].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, studies found that cse1 from this bacterium was expressed in specific growth condition (N-minimal medium) [27], which promoted the expression of the Salmonella pathogenicity island 2 genes [28]. Furthermore, the S. Typhi CRISPR-Cas locus is regulated by LeuO (LysR-type regulator), H-NS (heat-stable nucleoid-structuring protein), and LRP (leucine-responsive regulatory protein) [27,29], which are involved in pathogenesis [30][31][32][33][34][35]. The cas genes of the type I-C CRISPR-Cas system in Myxococcus xanthus seem to be strongly embedded within the regulatory circuits that control the fruiting-body formation process and are tightly regulated by various intercellular quorum-sensing (QS) signals and intracellular signaling cascades [36,37].…”
Section: Introductionmentioning
confidence: 99%
“…Since LeuO is the only global transcriptional regulator coded in the 25 kb deleted fragment of S. Typhi ΔF4, and LeuO is involved in different biological processes including detoxification, virulence, porin synthesis, and regulation of the CRISPR-Cas system in E. coli and Salmonella (De la Cruz et al 2007;Dillon et al 2012;Espinosa and Casadesús 2014;Guadarrama et al 2014;Hernández-Lucas et al 2008;Medina-Aparicio et al 2011;Westra et al 2010), a leuO mutant was obtained. Interestingly, the S. Typhi ΔF4 also lacks genes involved in thiamine transport (thiQP-tbpA).…”
Section: Discussionmentioning
confidence: 99%
“…Members of this family have been identified in many bacteria, including enteric pathogens such as Escherichia coli, Salmonella enterica serovar Typhimurium, Enterobacter cloacae , and Vibrio spp 23 . LeuO regulates a wide variety of genes that are involved in amino acid biosynthesis, catabolism of aromatic compounds, antibiotic resistance, nitrogen fixation, oxidative stress response, quorum sensing, and virulence 2427 . The structure of LTTR proteins includes an N-terminal DNA-binding helix-turn-helix motif and a C-terminal co-inducer-binding domain 23,28 .…”
Section: Introductionmentioning
confidence: 99%